Mechanism for collective property sharing in mixed marriage - Siti Alfisyahrin Lasori (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
This research discusses the mechanism of sharing joint assets for mixed marriage partners. The results of the study illustrate the applicable provisions with the facts that occur in the community regarding land ownership for Indonesian husbands or wives in mixed marriages. The research method used in this research is normative research method. The statutory approach and the conceptual approach The statutory approach is an approach using legislation and regulations. And the conceptual approach is to refer to legal principles. These principles can be found in scholarly views or legal doctrines . This study aims to analyze the mechanism for sharing joint assets in marriage, is based on the prevailing laws and regulations and provides legal certainty for the husband or wife of Indonesian citizens regarding the status of land ownership in joint assets for mixed marriages. Based on the results of the research, a conclusion is obtained that land ownership for Indonesian citizens due to mixed marriages without being equated with land rights for their foreign partners, which is only limited to use rights. Legal certainty for current Indonesian citizens to be entitled to land with ownership rights.